Enriqueta Vasquez and the Chicano movement : writings from El grito del norte - Longeaux y Vásquez, Enriqueta (Hispanic civil rights series., 2006)
Gathers columns from the Chicano newspaper "El Grito del Norte," where the author's fierce but hopeful voice of protest combined anger and humor to stir her fellow Chicanos to action as she drew upon her own experiences as a Chicana.